Association between myopia and relative peripheral refraction in children with monocular Tilted disc syndrome - Wang, Jiawei; Zhang, Shangzhu; Jiang, Huijun; Duan, Jialiang; Xi, Ruijie; Wang, Shaoyi; Wang, Jiangnan; Chai, Song (BMC ophthalmology, 2025)
This study aimed to investigate the refractive error and relative peripheral refraction in pediatric patients with monocular tilted disc syndrome. This single-center, prospective, cross-sectional, observational study included 49 patients from the Pediatric Ophthalmology Department of the Second Hospital of Hebei Medical University aged 5-17 years with monocular tilted disc syndrome. Eyes with tilted optic discs formed the study group, and contralateral eyes with normal discs served as controls, with mean spherical equivalents of - 3.24 D and - 0.47 D, respectively. Best-corrected visual acuity, spherical equivalent, axial length, tilt ratio, defined as the ratio of maximum to minimum disc diameters, and relative peripheral refraction, assessing myopia-related defocus were compared between groups. Pearson's correlation analysis assessed associations between optic disc tilt and spherical equivalent, axial length, and the total refraction difference value. Tilted optic discs were associated with significantly greater myopia (- 3.24 ± 1.83 D in tilted eyes and - 0.47 ± 0.72 D in non-tilted eyes, P <.001), longer axial length (24.59 ± 1.04 mm in tilted eyes and 23.45 ± 0.78 mm in non-tilted eyes, P <.001), and a higher tilt ratio (1.43 ± 0.05 in tilted eyes and 1.14 ± 0.04 in non-tilted eyes, P <.001). Discrepancies between tilted and non-tilted eyes were observed in the superior, inferior, and nasal quadrants, and the total refraction difference value (P <.001). In eyes with tilted disc syndrome, a negative correlation was found between the total refraction difference value and the spherical equivalent (P <.001). The tilt ratio of optic disc eyes was significantly greater than that of contralateral eyes and was negatively correlated with the spherical equivalent. There was a positive correlation between the tilt ratio and axial length (P <.001). Pediatric patients with monocular tilted disc syndrome exhibited longer axial lengths, more myopic spherical equivalent, and more positive relative peripheral refraction. A greater tilt ratio is associated with larger relative peripheral refraction and axial length, corresponding to more severe myopia.